BUILDING EMPLOYEE PERFORMANCE THROUGH EMPLOYEE ENGAGEMENT, WORK MOTIVATION, AND TRANSFORMATIONAL LEADERSHIP - Asih Niati; Citra Rizkiana; Edy Suryawardana (International Journal of Social Science, 2022)
BPR Agung Sejahtera is a financial institution that currently always improves performance. With changes in globalization and there are a lot of millennial employees, it will changes the attitudes, ways of working and lifestyles that will have an impact on employee performance. The purpose of this study was to determine the effect of transformational leadership and work engagement, whether it can be a motivation for work so it will improve the performance of millennial employees.This study was conducted at BPR Agung Sejahtara with 33 people as samples. Data collections were done by using questionnaire then analyze SPSS to test the validity and reliability and multiple regression analysis.The results of this study indicate that partially it can be concluded that Employee Engagement has a positive and significant effect on Work Motivation and Employee Performance. Transformational Leadership has a positive and significant effect on work motivation but does not have a positive and significant effect on employee performance. Work motivation also does not have a positive and significant impact on employee performance.